Egg production by the exotic shrimp Athanas dimorphus (Caridea: Alpheidae) in a harbor area in northeastern Brazil - Lima-Silva, Renata Fernanda; Soledade, Guidomar Oliveira; Pescinelli, Régis Augusto [UNESP]; Almeida, Alexandre Oliveira (Elsevier, 2023)
The shrimp Athanas dimorphus was recently recorded in the Western Atlantic, with successive records of introduction along the Brazilian coast. The present study aimed to investigate aspects related to propagule pressure of this shrimp, such as egg production, fecundity, egg volume, and the correlation between fecundity and female size. Additionally, we aimed to determine whether the species is established in the locality, in addition to inferring its ability as a propagule donor to adjacent regions. The following hypotheses were formulated: (1) the species has a reproductively active population in the studied area; (2) the studied population shows continuous reproduction throughout the year. Ovigerous females were collected monthly in the intertidal region of Praia do Paraíso, State of Pernambuco, northeastern Brazil, between April 2017 and March 2018. A total of 524 ovigerous females were sampled. Of these, 362 females carried normal eggs – 324 with eggs in stage I of embryonic development, 5 in stage II, 33 in stage III – 161 had abnormal eggs, and 1 carried eggs in the hatching stage. Only females carrying normal eggs were used in the analyses. The females’ carapace length and egg number and volume were measured and correlated. Mean fecundity in stage I was 63.2 ± 39.1, with egg number decreasing significantly between stages I and III. The mean egg volume increased significantly between stages I and III, presenting a total increase of 35%. The fecundity and size of females were positively correlated. Our results meet the two formulated hypotheses, indicating that A. dimorphus has a reproductively active population in the study area, with continuous reproduction throughout the year. As predicted by the propagule pressure theory, species with such characteristics are considered to be effective invaders, increasing their chances of reaching and establishing in new areas.
Keywords: Crustacea; Embryonic development; Exotic species; Propagule pressure; Reproduction